Analysis on characteristic of 3.3‐kV full SiC device and railway traction converter design. Issue 10 (22nd April 2022) - Ding, Rongjun; Dou, Zechun; Qi, Yu; Mei, Wenqing; Liu, Guoyou
Abstract: With the rapid development of wide‐band gap semiconductor chip and package technologies, the voltage class of commercial silicon carbide (SiC) device is gradually improved. This paper concentrates on the latest 3.3‐kV full SiC‐based metal oxide semiconductor field‐effect transistor (MOSFET) device and its application in railway traction. First, compared with the Si‐based insulated‐gate bipolar transistor (IGBT), the SiC‐based MOSFET shows lower switching loss but weaker short‐circuit capacity. Second, in the railway traction application, the SiC‐based MOSFET with high switching frequency could reduce the inverter loss, the harmonic loss and the noise of traction motor. Third, a well‐designed filter is necessary between the inverter and the motor to prevent the motor from terminal overvoltage and insulation problem, which are resulted from long cable and high d v /d t . Finally, a full‐SiC railway traction inverter prototype is built and tested, and shows obvious advantages on miniaturization and lightweight.